Testing an approach to screen and treat maternal depression through group therapy to improve newborn child outcomes in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2017)
This approach screens new mothers for depression and offers treatment through interpersonal therapy in groups (IPT-G). Maternal post-partum depression is associated with poorer child outcomes and IPT-G can alleviate depression symptom. This study will test whether cash transfers boost effectiveness of IPT-G for improving child outcomes in Ethiopia.